2016
DOI: 10.1002/2016tc004178
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the thermal evolution of the Corsican lower crust during Tethyan rifting

Abstract: Continental rifting requires thinning the continental lithosphere from ~120 km to <20 km by a series of processes which each impart a characteristic thermal signature to the extending lithosphere. Here high‐resolution thermochronology is used to trace the synrift thermal evolution within a lower crustal section of an upper plate hyperextended margin sampled in Corsica. Novel zircon, rutile, and apatite 206Pb/238U depth profiling coupled with garnet trace element diffusion modeling provide compelling evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 92 publications
(184 reference statements)
2
18
0
Order By: Relevance
“…This distribution supports the previously proposed paleogeographic location of the Santa-Lucia nappe in a para-autochthonous position to the East of the granitic batholith (Durand-Delga, 1984); or on the Ocean-Continent Transition (Fig. 14;Rossi et al, 2006;Beltrando et al, 2013;Seymour et al, 2016).…”
Section: The Tralonca Formation Of the Santa-lucia Nappesupporting
confidence: 90%
“…This distribution supports the previously proposed paleogeographic location of the Santa-Lucia nappe in a para-autochthonous position to the East of the granitic batholith (Durand-Delga, 1984); or on the Ocean-Continent Transition (Fig. 14;Rossi et al, 2006;Beltrando et al, 2013;Seymour et al, 2016).…”
Section: The Tralonca Formation Of the Santa-lucia Nappesupporting
confidence: 90%
“…The modeled thermal history is broadly consistent with recent thermochronological work that show that DDT is accompanied by an increase in thermal gradient in H-Block and hyperextension by an increase in thermal gradient in the sediments (Beltrando et al, 2015;Hart et al, 2017;Seymour et al, 2016;Smye et al, 2019;Smye & Stockli, 2014). While current seismic images and interpretations in Angola do not resolve the underplated magmatic additions, we do interpret a thickened oceanic crust and also magmatic additions at the OCT.…”
Section: Model Comparison With the Espirito Santo And Kwanza Sectionssupporting
confidence: 87%
“…Understanding the factors controlling decoupling, coupling and hyperextension should provide critical information on the mechanics of lithospheric necking and breakup. This exercise is critical at a time when new thermochronological data of fossil magma‐poor margins in the Alps and the Pyrenees have shown that reheating of the crust and the sediments occurs during lithospheric necking (thinning; Smye & Stockli, ; Beltrando et al, ; Seymour et al, ; Hart et al, ; Smye et al, ). Some authors suggest that these thermal events can be explained by rapid, active mantle upwelling during necking (Smye et al, ) and suggest that structures coupling fault in the crust and mantle are linked to both hyperextension and an actively upwelling mantle that could increase heat flow at the base of the extending crust and mantle lithosphere (Chenin et al, ; Gallacher et al, ; Hart et al, ; Huismans & Beaumont, , ; Royden & Keen, ; Svartman Dias et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Intragrain apatite U‐Pb increments were plotted as age spectra similar to data using Isoplot (Ludwig, ). Individual age spectra were stacked to examine overall U‐Pb topology within samples and to evaluate the thermal history of samples (Seymour et al, ).…”
Section: U‐pb and Trace Element Methodologymentioning
confidence: 99%